Fermentasi Kakao di Kelompok Tani Plea Puli Desa Bloro Kabupaten Sikka - Alberta, Maria; Bolly, Yovita Yasintha; Beja, Henderikus Darwin (LPPM Universitas Flores, 2023)
Bloro Village is one of the villages in Nita District, Sikka Regency, East Nusa Tenggara Province with the majority of the population working as farmers. The leading commodity in this village is Cocoa. The Plea Puli Farmers Group is one of the farmer groups involved in cocoa cultivation, including the seeding and processing of the results. The Plea Puli Farmers Group has a chocolate industrial house with production products in the form of cocoa powder and chocolate bars. To get a quality chocolate bar and cocoa powder products, you need to pay attention to post-harvest handling, namely cocoa fermentation. Because it is at this stage that determines the precursor to the distinctive taste of cocoa. However, the fact is that most farmers do not ferment properly. This program aims to provide education to farmers about post-harvest handling, especially cocoa fermentation. Through this activity, it is hoped that farmers can understand that to obtain good quality cocoa beans, the thing that must be considered is post-harvest handling, especially cocoa fermentation. This program begins with a discussion with several members of the Plea Puli Farmers Group and the preparation of an activity plan with the farmer group. Followed by the preparation stage, namely preparing tools and materials. At the implementation stage, activities began with socialisation about cocoa fermentation, then continued with harvesting, fruit sorting, ripening, fruit splitting, wet bean sorting, fermentation, and drying activities with the Plea Puli Farmers Group.